Pelvic organ prolapse: the impact on quality of life and psychological well-being - Antonio Simone Laganà; Valentina Lucia La Rosa; Agnese Maria Chiara Rapisarda; Salvatore Giovanni Vitale (Taylor & Francis Group, 2018)
The aim of this work is to propose a brief comment about the impact of pelvic organ prolapse on the quality of life and the psychological well-being of the affected women.